Production-consumption: the semiosis underlying human poiesis: notes towards a Marxist approach to the production cycle in contemporary capitalism - Llerena Borja, Oscar; Hernández Silva, Romel; Gallardo Apolo, Byron (Las Torres de Lucca. International Journal of Political Philosophy, 2026)
For Marxist materialism, the material reproduction of existence is the first condition of social life. Therefore, the economic sphere constitutes the core of civilized life, its own specific feature, as well as its original sin. The approach we present here seeks to address, using tools from critical Marxism, the semiosis born in the production-consumption circuit. We work from a Marxism that has abandoned Soviet pseudo-religious dogmatism and, thanks to this, has discovered a materialist ontology of the present. Economic life is thus the territory where the spirit of an era, its meaning and horizon, is produced. For those of us who live in a paradoxical time of crisis, a time that confronts human beings with their limits, the investigation of the social ontology that underlies the economic territory is decisive if we want to preserve any possibility of a future, that is, if we want to respond to the dramatic demands of our time, to the need for change, or a brake, on our planetary deployment. Any future humanity, any possibility that human beings build in the future, must scrutinize the economic territory in order to rediscover its uniqueness.
Keywords: Marxism; production; semiosis; politics; utopia